PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, UKURAN PERUSAHAAN, LEVERAGE DAN UKURAN KANTOR AKUNTAN PUBLIK (KAP) TERHADAP INTEGRITAS LAPORAN KEUANGAN - Intan Pratika; Nora Hilmia Primasari (Universitas Budi Luhur, 2020)
This study aims to determine the effect of independent commissioners, audit committees, company size, leverage and the size of public accounting firms on the integrity of financial statements. This research was conducted at property, real estate and building construction service companies listed on the Indonesia Stock Exchange (BEI) 2016-2019 period. The sampling technique used was purposive sampling. The number of sample companies was 37 companies with observation time of 4 years, so the total samples of 148 data. The analytical method used is multiple linear regression. The results of this study indicate that the size of a public accounting firm has a positive effect on the integrity of financial statements, while independent commissioners, audit committees, company size and leverage have no effect on the integrity of financial statements.